EVALUATION OF MORPHO-PHYSIOLOGICAL TRAITS OF TURKISH RICE GENOTYPES IN RESPONSE TO SALT STRESS UNDER IN VITRO CONDITIONS - H. Gungor; Y. Çikili; Z. Dumlupinar (Journal of Animal and Plant Sciences, 2019)
Salinity limits the rice germination and seedling growth at early growth stages. This study aimed to determine the morpho-physiological response of seventeen Turkish rice genotypes to four NaCl salinity stress (0, 40, 80 and 120 mM) under in vitro conditions during seed germination and early seedling stages. The effects of NaCl stress on water uptake, germination ratio, root length, shoot length, root fresh weight, root dry weight, shoot fresh weight, shoot dry weight, ion contens (Na, K, Ca and K/Na) for both root and shoot, and photosynthetic pigments (Chl a, Chl b, Chl a+b and carotenoid) in 17 rice genotypes were investigated in the experiment. The values of all traits were decreased by increasing the NaCl levels (p ≤ 0.05), and genotype specific variations were identified under salt stress (p ≤ 0.05). The investigated traits were decreased by salt stress including germination rate (43.1%), root and shoot lengths (80.3 and 78.4%), root fresh and dry weights (85.9 and 83.1%), shoot fresh and dry weights (70.4 and 64.9%), root and shoot K/Na (97.8 and 98.6%), and chl a (44.3%). According to genotype, genotype ´ environment (GGE) biplot analysis, principal components (PC1 and PC2) represented (38.02 and 18.39%, respectively) 56.41% of the total variation among the genotypes under salt stress. Gönen cultivar showed greater performance for the investigated traits, and had the highest salt tolerance among the cultivars. It is concluded that Gönen cultivar could be recommended for the region.
Keywords: GGE biplot; ion contents; photosynthetic pigments; rice; salinity stress